Prospects for Energy Demand Management in Russian Regions - Dzyubaa, Anatolyy P.; Solovyeva, Irina A. (Economy of Regions, 2021)
In order to improve the energy efficiency in industrialised countries, energy demand management technologies are being introduced. In Russia, energy consumption is characterised by high natural gas usage. A decrease in demand volatility leads to the reduction of energy costs for industrial consumers. These factors indicate the feasibility of electricity and natural gas demand management. Simultaneously, Russian regions significantly differ in terms of the prospects for introducing integrated demand management. To examine the problem, we used statistical analysis, mathematical modelling and a method for constructing perceptual maps. Parameters of electricity and natural gas demand management in Russian regions were examined. As a result, we developed a methodology to assess the possibility of implementing energy demand management in various entities. This method is based on a system of indicators considering absolute and relative density of regions’ electricity and natural gas demand, industrial energy consumption, and natural gas used to generate electricity. The analysis of the relevant indicators allowed us to construct energy demand volatility maps and a matrix indicating the effectiveness of proposed management tools. The research findings can be used when developing targeted programmes for energy demand management at the regional and federal levels.